Simple Accounting Assistance and Training Activities, Post-COVID-19 for Small Business in Sei Silau Tua Village, Asahan Regency - Lucky Satria Pratama; Tengku Syarifah; Anshari Putra; Halimatussaddiah Marpaung; Eddy Pangidoan (Budapest International Research and Critics University, 2022)
Bookkeeping is important and is one of the supporting factors for the success of a small business, especially in rural communities, with simple accounting that can help village communities in estimating the potential of small business to earn profits. In the first implementation strategy stage, researching the situation in Sei Silau Tua Village, the second identifying problems, and third involving partners to solve problems in the village. Village officials, Asahan District Government, village communities and related stakeholders must be able to work together to improve road facilities and build strong dams which later on the village community can do marketing outside the village. By doing simple accounting, financial records that follow applicable standards can later be used if the small business owner wants a loan to increase or expand his business activities. Therefore, it is necessary to carry out similar activities for other small business owners so that micro, small and medium enterprises can develop in Sei Silau Tua Village.